A Novel Mobile App Based College Event Management System - Lavania, Geerja; Kumar, Neeraj; Arya, Vivek; Kumari, Meet; Sharma, Neha; Singh, Pardeep (2023 4th International Conference on Smart Electronics and Communication (ICOSEC), 2023)
The school has many events and celebrations throughout the year. All work for events and festivals is done by hand. The "Online Event Management" project is an Android application that allows you to remotely create, cancel, edit and manage online events. It allows school administrators to add, remove or edit events and allows students to view all events available in each school. It allows students to record and view all activities in this app and you can pay through the app. This program reduces the need for information and saves time in running a smooth event. Anyone can follow any student and keep track of many things through this app. The main purpose of this app is to keep all college students aware of everything going on at the university, further reducing the work of books and digitizing everything.